Discovering the relevance of the personality of the destination brand - a literature review - Cardoso, António; Fomina, Irina; Dimitrova, Monika; Sousa Pereira, Manuel (Marketing & Tourism Review, 2022)
Brand personality is highly significant for creating brand loyalty to withstand pressure in the highly competitive environment. Due to the cosmopolitanism and affordable traveling, people have become jaded and hard to surprise, thus, cities’ authorities must create smart destination brand personalities to attract more visitors. The aim of this paper is to gather the most popular city branding tools, trends and similarities through bibliometric study and present a broad view of the researches that have been conducted regarding destination brand personality. As a methodology, it uses a qualitative analysis which was made by exploring a scientific database. A common ground for all previous research on the topic tends to be the 5 Aaker’s Brand Personality Scale dimensions (1997) or extended to the 6 dimensions scale used in the most recent studies. The limitations of the research can indicate that there are still gaps in the literature connected to this topic, and the paper includes suggestions to fill them in. Most of the studies had focused on tourists’ perspective, and do not take residents’ views into consideration. As main results, we found that, research shows that young residents should be more involved into the destination’s branding process. Also, social media platforms as a marketing tool for promoting cities and gathering feedback from locals and tourists are understudied.